Hubungan Dukungan Keluarga Terhadap Kunjungan Antenatal Care Pada Ibu Hamil Trimester III Di Puskesmas Godean I Kabupaten Sleman - Yoanda Miftahul Jannati; Fathiyatur Rohmah (CV. ITTC INDONESIA, 2025)
The indicator used to describe pregnant women's access to prenatal services is the K1 (first visit) coverage rate, while the K4–K6 (fourth to sixth visits) coverage rates are used to assess the quality of services. Nationally, the K4 coverage rate in 2022 was 86.2%, which is close to the RPJM target of 90%. In Yogyakarta Province, the K4 coverage rate was 55.5%. Similarly, the K6 coverage rate in 2022 was 70.9%, while in Yogyakarta Province, it was 49.0%. The K4 coverage rate in Yogyakarta Province has not yet reached the target of 83.8%. The K4 coverage rates by region are as follows: Sleman Regency at 83.7%, Bantul Regency at 81.1%, Kulon Progo Regency at 93.2%, Gunung Kidul Regency at 83.9%, and Yogyakarta City at 82.8%. These figures indicate that the K4 coverage target has not been fully achieved. This study aims to investigate the relationship between family support and antenatal care visits among third- trimester pregnant women at Puskesmas (Community Health Center) Godean I in Sleman Regency. This study employed correlational analytic method with cross- sectional approach. Sampling was conducted using the accidental sampling technique, involving 46 respondents. Data were collected using questionnaires and maternal and child health (MCH) books. Data analysis was performed using the Chi-Square test. The results of the study showed a p-value of 0,005 < 0,05. This indicates a significant relationship between family support and antenatal care visits. The strength of the relationship falls within the moderate category, with a contingency coefficient value of 0.413. This study concludes that there is a relationship between family support and antenatal care visits among third- trimester pregnant women at Puskesmas Godean I in Sleman Regency. The researchers recommend that families provide optimal support, including instrumental, informational, emotional, and appreciative support, to encourage pregnant women to attend antenatal care visits regularly. This ensures the well- being and health of both the mother and the fetus.